Elucidating mechanism of glycosylation reactions with computational methods - Guo, Aoxin (Nanyang Technological University, 2021)
Glycosylation reaction is the central reaction for chemically constructing a manifold of biologically active molecules. An understanding of the mechanism of the glycosylation reaction promise to guide the rational design of glycosyl donors, acceptors, and addictive agents for accomplishing high stereo- and regio- selectivity, which has been keenly pursued by glycochemists for decades. With the striding developments in computer hardware, algorithm, physical theory, and numerical methods over the past decades, simulation of chemical systems comprising up to ~200 atoms, which encompass a large fraction of the experimentally synthesized organic molecules, with quantum mechanical (QM) theory, especially the density functional theory (DFT) based methods, could now be achieved on a practical timescale and cost, with satisfactory reliability and accuracy. DFT calculations enable predictions of the geometry structures, energies, and spectroscopic properties of the reagents, products, intermediates, and most importantly, transition states, which are not amenable to experimental characterizations with most of the routinely employed techniques and have become a powerful tool for rationalizing the reaction mechanism for organic reactions. Following a brief background introduction in Chapter 1, Chapter 2 presents a theoretical investigation on the mechanistic details giving rise to acceptor-dependent stereoselectivity of glycosylation by the 2-cynobenzyl glucose donor developed by Le Mai Huang and Liu. Then, Chapter 3 presents a novel phosphazene superbase catalyzed regio- and stereoselective glycosylation of alcohols by glycal donors, as well as the theoretical investigations on the mechanism of the reaction leading to the 4-position-substituent-dependent stereoselectivity and the regioselectivity. Finally, Chapter 4 presents the development of a novel alpha-selective glycal glycosylation reaction catalyzed by a simple iridium-metal catalyst, and the application of DFT theory calculations in elaborating the mechanisms giving rise to the alpha-stereoselectivity of the reactions.